Use of Artificial Intelligence in Marketing Management: Opportunities and Challenges - Ismail Razak (SEAN Institute, 2023)
This research examines the use of artificial intelligence (AI) in the context of marketing management, exploring the opportunities and challenges that arise with the integration of AI technology in marketing strategy. This research aims to investigate how the implementation of artificial intelligence can increase efficiency, accuracy and responsiveness in marketing decision making. The research methodology involves analyzing literature to identify current trends in the use of AI in marketing management with a qualitative approach. The research results show that the implementation of artificial intelligence (AI) in marketing management has a positive impact by increasing the personalization of messages and offers, optimizing operational efficiency through automating routine tasks, and providing deep insight into consumer behavior and market trends. Nonetheless, challenges such as customer privacy concerns and reliance on representative data quality were also identified. Therefore, awareness and effective management of these aspects are key in ensuring the successful implementation of AI in marketing strategies and achieving sustainable business goals.